Efficiency of Physico- chemical constants vis×³- a vis×³ Reversed- phase thin layer chromatography (RP-TLC) in evaluating the quality of fat in market samples of paneer - Sharma, vivek; Kandho, Rakesh; Arora, Sumit; Rao, Priyanka Singh; Singh, Richa; Gupta, Hariram (Indian Journal of Dairy Science, 2017)
Paneer is a coagulated milk product obtained by heating and acidulation, followed by filtration and pressing. Milk fat is one of the costliest components in paneer, which attracts unscrupulous people in the trade of paneer to add vegetable oil/ fat emulsion to skimmed milk and prepare paneer. Generally recommended tests to check the quality of milk fat do not help much in assuring the quality of paneer fat. Recent study revealed that by employing RP- TLC approach the minimum 5% level of adulteration of milk fat in paneer could be detected The analysis of market samples of paneer from organized sector revealed that all the samples from organized sector met the physico- chemical paramters of milk fat as specified by FSSR (2011). On the contrary, in case of unorganized sector 18.75 %, 6.25% and 31.25% samples failed on the basis of RM value, Polenske value and BR reading, respectively. On employing RP-TLC analysis, paneer fat samples i.e. 43.75% from unorganized sector and 28.57% from organised sector showed presence of vegetable oil/ fat. Â In the present investigation it was found that market samples of paneer both form organised and unorganised sector had some problem of fat adulteration which otherwise went unchecked in organised paneer samples, using conventional methods of testing.